2018
DOI: 10.2135/cropsci2017.11.0703
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Balance is Affected by Protein Concentration in Soybean

Abstract: Soybean [Glycine max (L.) Merr.] produces a high‐quality protein that provides an appropriate balance of amino acids for monogastric animals. It has been reported that the relative abundance of some essential amino acids may be reduced in soybean with high protein concentration. A dilution of essential amino acids in soybean protein would lead to a reduction in the value of that protein to the end user, and undefined variation in amino acid balance of soybean would lead to poorly balanced animal rations. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 38 publications
(98 reference statements)
3
19
0
Order By: Relevance
“…8 and Pfarr et al . 29 reported that most of the EAAs decreased as protein concentration increased, while glutamic acid and arginine increased in relative abundance. Our results showed that increases in protein produce a more than proportional increase in cysteine and close to a proportional increase in methionine, showing that increases in protein would partially overcome the low concentration of these deficient AAs.…”
Section: Discussionmentioning
confidence: 99%
“…8 and Pfarr et al . 29 reported that most of the EAAs decreased as protein concentration increased, while glutamic acid and arginine increased in relative abundance. Our results showed that increases in protein produce a more than proportional increase in cysteine and close to a proportional increase in methionine, showing that increases in protein would partially overcome the low concentration of these deficient AAs.…”
Section: Discussionmentioning
confidence: 99%
“…4 ). Using protein as a predictor of the AA changes over time was previously reported 9 , but considering only modern genotypes rather than a historical set as presented in this current study. Our findings show similar relationships for some AA changes such as glutamic acid and arginine relative-to-protein genetic gain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between seed protein and AA concentration varies according to each AA. For instance, lysine, methionine, cysteine, tryptophan, and threonine are negatively correlated with seed protein concentration, whereas arginine and glutamic acid increase with seed protein concentration 9 , 13 . In China, significant negative trends for glutamic acid, histidine, and arginine were reported in soybean genotypes released between 1923 and 2007 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been recommended that protein quality is based upon essential amino acid content. However, for many reasons, animal feed and human food markets have only recently begun assessing accordingly [5,18,19]. Equipment required for accurate amino acid measurement and the diversity of markets for amino acids makes it difficult for supply chain evaluators like elevator operators to appraise amino acid content on site.…”
Section: Essential Amino Acidsmentioning
confidence: 99%